Provocations for a New Epistemology: Conversations with Franz Hinkelammert - Solórzano Alfaro, Norman (2025)
In these reflections, a heartfelt tribute is paid to the teacher and friend Franz Hinkelammert, while proposing the relevance of a project to be carried out: reconstitute the epistemology of the empirical sciences, in general, and of the social sciences in particular. For these purposes, from the reading of the materials that Hinkelammert has shared for more than 50 years, brief and preliminary notes are made on the role of the subject and transcendental reflection in the constitution of the empirical sciences.